Determinants of employees’ financial well-being: the moderation effect of work sectors - Sabri, Mohamad Fazli; Falahati, Leila; Masud, Jariah; Paim, Laily (Malaysian Consumer and Family Economics Association, 2013)
The purpose of this study is to examine factors affecting financial well-being among public and private employees in Malaysia. The results of this study can be used for better understanding on the relationships between and among determinants of financial well-being by highlighting the relationships among financial literacy, financial behavior, financial management, financial problems, and financial stress. Samples were selected using multistage sampling technique among employees in public and private sectors. A total of 2,000 completed questionnaires were analyzed using path analysis to identify direct and indirect effects on financial well-being. The results indicate that financial behavior, financial management, financial problems and financial stress are significant predictors of financial well-being among employees in public and private sectors. In contrast, financial literacy contributes to predict financial well-being among public sectors but not among private sectors. Findings from this study have important implication with respect to the need of workplace financial education.